Microwave-assisted synthesis of biologically relevant steroidal 17-exo-pyrazol-5'-ones from a norpregnene precursor by a side-chain elongation/heterocyclization sequence - Mótyán, Gergő; Mérai, László; Kiss, Márton Attila; Schelz, Zsuzsanna; Sinka, Izabella; Zupkó, István; Frank, Éva (Beilstein Journal of Organic Chemistry, 2018)
Multistep syntheses of novel 17β-pyrazol-5'-ones in the Δ5-androstane series were efficiently carried out from pregnenolone acetate. A steroidal 17-carboxylic acid was first synthesized as a norpregnene precursor by the bromoform reaction and subsequent acetylation. Its CDI-activated acylimidazole derivative was then converted to a β-ketoester containing a two carbon atom-elongated side chain than that of the starting material. A Knorr cyclization of the bifunctional 1,3-dicarbonyl compound with hydrazine and its monosubstituted derivatives in AcOH under microwave heating conditions led to the regioselective formation of 17-exo-heterocycles in good to excellent yields. The suppression of an acid-catalyzed thermal decarboxylation of the β-ketoester and thus a significant improvement in the yield of the desired heterocyclic products could be achieved by the preliminary liberation of the arylhydrazines from their hydrochloride salts in EtOH in the presence of NaOAc. The reaction rates were found to depend on the electronic character of the substituent present in the phenylhydrazine applied. The antiproliferative activities of the structurally related steroidal pyrazol-5'-ones and their deacetylated analogs were screened on three human adherent breast cancer cell lines (MCF7, T47D and MDA-MB-231): the microculture tetrazolium assay revealed that some of the presented derivatives exerted cell growth inhibitory effects on some of these cell lines comparable to those of the reference compound, cisplatin.
Keywords: antiproliferative activity; Knorr reaction; microwave; pyrazol-5-ones; steroids